Professor Norman Farnsworth Dies at 81 - Cock, I. E. (Pharmacognosy Communications)
Prof. Norman R. Farnsworth, a renowned medicinal plant researcher and a giant in the field of pharmacognosy, died September 12, 2011 in Chicago. Dr Farnsworth graduated with a degree in pharmacy from Massachusetts College of Pharmacy in 1953. He subsequently undertook postgraduate studies in pharmacognosy at the University of Pittsburgh, receiving his PhD in 1959. He was instrumental in instituting a pharmacognosy PhD program at the University of Pittsburgh and was its inaugural chair. In 1970, Prof. Farnsworth accepted a post in the College of Pharmacy at the University of Illinois, Chicago, serving as Departmental Head from 1970-1982. In this role he mentored more than 100 PhD students, 30 MS students and 30 postdoctoral fellows.